Evaluating The Role of Career Development Practices in Enhancing Employee Retention in the Hospitality Industry - Shreya, Shreya; Yadav, Preeti (Journal of Neonatal Surgery, 2025)
One of the most significant challenges that the hospitality business in Rajasthan, which is a famous center for tourism and cultural heritage in India, is facing is the problem of keeping its personnel. Turnover among employees has a detrimental influence on both the quality of service and the efficiency of operations. The hotel industry in Rajasthan is the focus of this research, which investigates the influence that career development methods have in boosting employee retention. The purpose of this study is to offer industry stakeholders with practical insights by conducting an analysis of a variety of career development methods on the basis of how workers assess the success of these techniques. The results highlight the significance of organized training programs, mentoring, possibilities for career growth, and skill upgrading activities in the process of creating workforce stability..